Two detoxification enzyme genes, CYP6DA2 and CarFE4, mediate the susceptibility to afidopyropen in Semiaphis heraclei - Fu, Xiaochen; Xue, Chao; Wang, Xin; Wang, Aiyu; Zhu, Yanwei; Yang, Yuanxue; Zhang, Yun; Zhou, Yun; Zhao, Ming; Shan, Chenggang; Zhang, Jianhua (Frontiers in Physiology, 2024)
IntroductionSemiaphis heraclei is an important economic pest affecting Caprifoliaceae and Apiaceae plants, and chemical control is still the main effective control method in the field. Afidopyropen is a new type of pyridine cyclopropyl insecticide, which can effectively control piercing-sucking mouthparts pests and is suitable for pest resistance management. However, the detoxification mechanism of S. heraclei to afidopyropen is still poorly cleared.MethodsThe insecticidal activity of afidopyropen against S. heraclei and the enzyme activity assay and synergism bioassay were evaluated. The detoxification enzyme genes were obtained by transcriptome and validated by quantitative real-time PCR (RT-qPCR). Furthermore, RNA interference was used to study the functions of detoxification enzyme genes.ResultsThe activities of cytochrome P450 monooxygenases (P450s) and carboxylesterases (CarEs) were significantly increased under afidopyropen treatment. The toxicity of afidopyropen against S. heraclei was significantly increased after application the inhibitors of piperonyl butoxide and triphenyl phosphate. Sixteen P450 genes and three CarE genes were identified in the transcriptome of S. heraclei. The RT-qPCR results showed that eleven P450 genes and two CarE genes were significantly upregulated under afidopyropen treatment, and the expression of CYP6DA2 and CarFE4 was upregulated by more than 2.5 times. The expression pattern of CYP6DA2 and CarFE4 was further analyzed in different developmental stages of S. heraclei and knockdown of CYP6DA2 and CarFE4 significantly increased the susceptibility of S. heraclei to afidopyropen.ConclusionThe results of this study uncover the key functions of CYP6DA2 and CarFE4 in the detoxification mechanism of S. heraclei to afidopyropen, and provide a theoretical basis for the scientific use of afidopyropen in the field.